Artificial Intelligence in Education - Okhanashvili, Svimon (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Learning and teaching are complex mental and physical processes that require certain skills, willpower, experience, purpose, desire, health, and mood, in addition to the learning environment, the methodological level of textbooks, the quantity and quality of knowledge, and the experience of the teacher. It should be noted that among all technological achievements, artificial intelligence is a powerful tool for improving the quality of education. It has transformed traditional teaching methods by introducing new approaches and creating educational systems with quick access to essential resources. Artificial intelligence can contribute to education in various ways: Personalized Learning: AI-powered systems, such as multimedia platforms and educational applications (e.g., Knewton, ALEKS), use special algorithms to assess and analyze students' knowledge. These systems identify students' weaknesses and strengths, providing personalized assignments to help develop their skills. Interactive Simulations and Virtual Labs: In subjects like physics, chemistry, and biology, virtual labs (e.g., PhET Interactive Simulations, Labster) allow students to perform experiments in a safe and interactive environment. Tutors and Automatic Problem Solving: AI helps students solve math problems by explaining each step, guiding them through the process, and enhancing their understanding. Visualizations and Animations: In subjects such as biology and chemistry, AI can animate complex processes, making them easier to understand. Automated Assignment Grading: AI systems provide quick and accurate grading with instant feedback, helping students learn more efficiently. Lesson Adaptation and Progress Monitoring: AI can monitor students' learning progress and suggest relevant materials to help them better understand difficult topics.